2020
DOI: 10.1177/1040638720906451
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular squamous cell carcinoma in 2 psittacines

Abstract: A unilateral, malformed gnathotheca in a green-winged macaw ( Ara chloropterus) was managed for 16 mo with periodic beak trims. Biopsy of the affected beak did not identify an underlying cause; however, at postmortem examination, a densely cellular neoplasm invaded the mandible from the beak, dissecting and effacing the cortex and trabecular bone and inciting periosteal proliferation. There was no evidence of metastasis. Neoplastic cells were strongly immunopositive for cytokeratin AE1/AE3, consistent with squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…In birds, a variable degree of keratinization, invasion of the adjacent tissues, and metastasis have been reported in SCCs in different body locations [ 9 , 11 , 12 , 16 ]. The cytoplasm of neoplastic cells in the footpad was strongly positive for cytokeratin (CK), a remarkable feature also observed in SCCs in the foot of a pink-backed pelican [ 14 ] and in the mandible of two psittacines [ 7 ].…”
mentioning
confidence: 99%
“…In birds, a variable degree of keratinization, invasion of the adjacent tissues, and metastasis have been reported in SCCs in different body locations [ 9 , 11 , 12 , 16 ]. The cytoplasm of neoplastic cells in the footpad was strongly positive for cytokeratin (CK), a remarkable feature also observed in SCCs in the foot of a pink-backed pelican [ 14 ] and in the mandible of two psittacines [ 7 ].…”
mentioning
confidence: 99%
“…2,11,40 There are a few, scattered reports of alimentary SCC in psittacines that include an ingluvial SCC in a cockatiel, mandibular SCCs in a green-winged macaw ( Ara chloropterus ), a black-headed caique ( Pionites melanocephalus ) and a Buffon’s macaw ( Ara ambigua ), and esophageal SCCs in 2 Amazon parrots ( Amazona aestiva and Amazona farinosa ). 10,18,19,35 Retrospective reviews of case submissions to veterinary diagnostic laboratories also revealed a low prevalence of these neoplasms, including cases of oral SCC in an unspecified psittacine and in a red-shouldered macaw ( Diopsittaca nobilis ). 6,10,26…”
Section: Discussionmentioning
confidence: 99%
“…10,18,19,35 Retrospective reviews of case submissions to veterinary diagnostic laboratories also revealed a low prevalence of these neoplasms, including cases of oral SCC in an unspecified psittacine and in a red-shouldered macaw ( Diopsittaca nobilis ). 6,10,26…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations